2019
DOI: 10.3390/agronomy9010028
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biostimulant, Belonging to Protein Hydrolysates, Mitigates Abiotic Stress Effects on Maize Seedlings Grown in Hydroponics

Abstract: The main challenge to agriculture worldwide is feeding a rapidly growing human population, developing more sustainable agricultural practices that do not threaten human and ecosystem health. An innovative solution relies on the use of biostimulants, as a tool to enhance nutrient use efficiency and crop performances under sub-optimal conditions. In this work a novel biostimulant (APR®, ILSA S.p.A., Arzigano VI, Italy), belonging to the group of protein hydrolysates, was supplied to maize seedlings in hydroponic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 44 publications
2
38
0
Order By: Relevance
“…In another study, Botta et al [84] observed that lettuce plants treated with an animal-based protein hydrolysed had a higher fresh and dry weight compared with the control. Generally, they can induce plant defense responses and increase plant tolerance to many abiotic stresses, as reported by several authors [85][86][87][88].…”
Section: Classification Of Biostimulants In Categoriesmentioning
confidence: 72%
See 1 more Smart Citation
“…In another study, Botta et al [84] observed that lettuce plants treated with an animal-based protein hydrolysed had a higher fresh and dry weight compared with the control. Generally, they can induce plant defense responses and increase plant tolerance to many abiotic stresses, as reported by several authors [85][86][87][88].…”
Section: Classification Of Biostimulants In Categoriesmentioning
confidence: 72%
“…4.3.1.5) [92]. The effect of biostimulant application on PAL activity and on the expression of genes encoding for this enzyme was observed by several authors [56,88,89] and references therein, even if at present it is not possible to define if this is a direct or indirect effect. Because of the diversity of source materials and extraction technologies, the mode of action of these products is not easily determined [55].…”
Section: Classification Of Biostimulants In Categoriesmentioning
confidence: 98%
“…These former molecules present in seaweed and PH-based biostimulants may have triggered a signal transduction pathway through elicitation of endogenous phytohormone synthesis, thus leading to a higher crop productivity compared to untreated-baby lettuce plants [19,20]. Another possible mechanism of action (indirect mechanism) behind the stimulation of LAI and marketable fresh yield could be the modulation of the root system architecture in terms of root biomass, root volume and length and higher root branching triggered by tryptophan in LDPH and auxins in SwE, which improved nutrient uptake/translocation/assimilation, leading to a higher agronomical performance [12,19,41,42]. Our results are in agreement with those of Carillo and co-workers [22] who reported that foliar application of LDPH at a rate of 4 mL•L −1 under suboptimal N fertilization conditions (0 and 15 kg N•ha −1 ) increased the fresh yield of greenhouse spinach through an increase of the nutritional status (higher macronutrient accumulation), better photosynthetic activity and improving the total acid content.…”
Section: N0 N10 N20 N30mentioning
confidence: 99%
“…The phytochemical homeostasis requires enzymatic activities leading to a stabilization of the concentration of antioxidants which show an increase both in response to free radical production [19,31] and when K and Mg in the tissues are high [31]. In this respect, the protection against oxidative stresses in maize plants was primed by both protein hydrolysate and plant extract based biostimulant through the expression of superoxide dismutases activity-regulating genes [54], which catalyze the enzymatic dismutation of superoxide to H 2 O 2 [55]. The application of protein hydrolysates in greenhouse conditions encouraged the synthesis of ascorbate, p-coumaric, chlorogenic acid, capsaicin and antioxidant activity in Capsicum chinensis L. fruits [19], as well vitamin C in tomato fruits [18,31].…”
Section: Antioxidant Activity and Bioactive Contentmentioning
confidence: 99%